Taiwan in the Asia-Pacific in the 1990s (Allen & Unwin, 1994)
This book is about: Taiwan's domestic political reforms, Institutional change and power realignment; Emerging Taiwanese identify in the 1990s; The Rise of Island-China separatism; ...